MUF302 : Recital / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2024)
This course is culmination of students’ knowledge and skills gained over the course of their studies. This course exposes them to the common practices of music performance such as technical abilities, musicianship, organizing skills, time management and teamwork. Students will be performing, organizing and managing their recital.